Reynolds number k-ε modeling by using the direct numerical simulation (DNS) data - Abdul-Hussein, Ahmed (University of Thi-Qar Journal of Science, 2008)
The constant C and the near-wall damping function f in the eddyviscosityrelation of the k-ε model are evaluated from direct numericalsimulation (DNS) data for developed channel and boundary-layer flow, eachat two Reynolds numbers. Various existing f µµmodel functions are comparedwith the DNS data, and a new function is fitted to the high-Reynolds-numberchannel flow data. The ε-budget is computed for the fully developed channelflow. The relative magnitude of the terms in the ε-equation is analyzed withthe aid of scaling arguments, and the parameter governing this magnitude isestablished. Models for the sum of all source and sink terms in the ε- equationare tested against the DNS data, and an improved model is proposed.